Studies on Palmyrene Sculpture - Bobou, Olympia; Vestergaard Jensen, Jesper; Breintoft Kristensen, Nathalia; Raja, Rubina; Randeris Thomsen, Rikke (Brepols, 2021)
This volume presents the first English translation of Harald Ingholt’s seminal work <span class=